Socio-Cultural Component of Socialization of Foreign Students - Бовен, Цінь (Київський національний університет імені Тараса Шевченка, 2021)
The analysis of the process of socialization of foreign students is carried out. The role of the socio-cultural component of socialization of foreign students is substantiated. The role of the socio-cultural aspect in the process of human socialization is highlighted. The analysis of the last sources and publications is carried out. It is noted that socialization is considered as a set of certain components: social adaptation involves the process of adaptation to changing conditions or requirements of society; education involves specially organized, controlled influences; individualization involves analysis and interaction with natural influences. The multifaceted definition of "status" is considered as a state of an individual in a certain social group, which has a number of components that determine the features of a set of status-role functions of each student. An important component of modern society - socio-cultural space. The peculiarities of the socio-cultural space are determined by the development of new technologies and means of communication. The main characteristics of the socio-cultural space of modern society as a new level of overcoming cultural barriers and cultural differences of intercultural contacts are described. The result of the socio-cultural component of socialization determines the presence of values and spiritual landmarks of society. The structure of the socio-cultural component of the socialization of a foreign student is represented: personality as a subject of interaction; society as a set of individuals interacting with socio-cultural relations and processes; culture as a set of values, values and norms possessed by individuals who are in interaction, and a set of carriers that objectify, socialize and reveal these values. The study of the socio-cultural component of socialization as a scientific phenomenon takes place at four levels: methodological, species, factor, status. It is concluded that the socio-cultural component of the socialization of foreign students depends on the characteristics of the educational and cultural environment of the institution of higher education, and on the cultural environment of society as a whole. These two factors are designed to provide favorable conditions for the active entry of a foreign student into a new society.

Здійснено аналіз процесу соціалізації іноземних студентів. Обґрунтовано роль соціокультурної складової соціалізації іноземних студентів, яку розглянуто як сукупність певних компонентів: соціальної адаптації, соціального виховання, індивідуалізації. Досліджено багатогранну дефініцію "статус" як стан індивіда у складі певної соціальної групи, яка володіє низкою складових, що визначають особливості набору статусно-рольових функцій кожного студента. Виокремлено важливу складову сучасного суспільства – соціокультурний простір та його роль у процесі соціалізації іноземних студентів. Зроблено висновок, що соціокультурна складова соціалізації іноземних студентів залежить як від особливостей освітньо-культурного середовища закладу вищої освіти, так і від соціокультурного середовища суспільства в цілому.
Соціокультурна складова соціалізації іноземних студентів
Keywords: socialization; sociocultural space; status; status-role functions; adaptation; social education; individualization; соціалізація; соціокультурний простір; статус; статусно-рольові функції; адаптація; соціальне виховання; індивідуалізація